Reducing vehicle cold start emissions through carbon pricing: evidence from Germany - Manuel Frondel; Clemens Marggraf; Stephan Sommer; Colin Vance (Environmental Research Letters, 2021)
A large proportion of local pollutants originating from the road transport sector is generated during the so-called cold-start phase of driving, that is, the first few minutes of driving after a car has stood inactive for several hours. Drawing on data from the German Mobility Panel (MOP), this paper analyzes the factors that affect the frequency of cold starts, approximated here by the number of car tours that a household takes over the course of a week. Based on fixed-effects panel estimations, we find a negative and statistically significant effect of fuel prices on the number of tours and, hence, cold starts. Using our estimates to explore the spatial implications arising from fuel price increases stipulated under Germany's Climate Programme 2030, we find substantial impacts on the number of avoided tours even for modest fuel price increases of 20 cents0.167emper liter, particularly in urban areas. This outcome lends support to using carbon pricing as a means to improve both global climate and local air quality, pointing to a co-benefit of climate policy.
Keywords: 330; German Mobility Panel; fuel prices; car use